Transcellular Passage of Neisseria gonorrhoeae Involves Pilus Phase Variation - Ilver, Dag (American Society for Microbiology, 1998)
Piliated and nonpiliated Neisseria gonorrhoeae organisms were added on top of confluent layers of HEC-1-B cells, each maintained on a microporous Transwell-COL membrane. The bacteria released into the lower chamber were characterized with respect to the following virulence determinants: pili, which mediate adherence to target host cells; PilE, the major pilus subunit protein; and PilC, which is involved in pilus biogenesis and adherence. Even if >99% of the added bacteria of N. gonorrhoeae MS11 were piliated, bacteria recovered on the other side of the cell layer were predominantly nonpiliated. The recovered clones still expressed unassembled PilE protein, but 50% had lost PilC production. Nonpiliated gonococci, in which the 5′ end of pilE had been deleted, were released in reduced numbers, and piliated recA bacteria added to the cell layer were not released at all, at time points when piliated recA(+) clones were found at high numbers in the lower chamber. Our data indicate that bacteria producing unassembled PilE protein are selected for during passage through an epithelial cell layer. The finding that the pilE gene sequence was altered in the transmigrants suggests that pilin sequence variation is involved in the transcellular passage of N. gonorrhoeae.